Corporate intranet platform – open and commercial solutions comparison - Czarny, Konrad (Journal of Computer Sciences Institute, 2020)
The article presents a comparison of CMS systems that can be used when creating an intranet platform for a corporate network. The primary goal is to indicate which of the technologies is the most suitable for a large international corporation. Two open (WordPress, Drupal) and commercial (SharePoint, Confluence) tools were included in the study.